2007
DOI: 10.1039/b700547d
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and applications of genetic circuits

Abstract: In the field of synthetic biology, recent genetic engineering efforts have enabled the construction of novel genetic circuits with diverse functionalities and unique activation mechanisms. Because of these advances, artificial genetic networks are becoming increasingly complex, and are demonstrating more robust behaviors with reduced crosstalk between defined modules. These properties have allowed for the identification of a growing set of design principles that govern genetic networks, and led to an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Finally, this work and our previous reports demonstrated that the genetic screen and selection that we developed could be used to engineer the components of quorum-sensing systems to change various properties, and these engineered quorum-sensing systems are expected to be useful in synthetic biology and metabolic engineering. [33] Experimental Section Bacterial strains, media, chemicals and culture conditions: E. coli strain Top10F' was used for all experiments. Unless otherwise stated, all chemicals were purchased from Sigma-Aldrich (St Louis, MO, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this work and our previous reports demonstrated that the genetic screen and selection that we developed could be used to engineer the components of quorum-sensing systems to change various properties, and these engineered quorum-sensing systems are expected to be useful in synthetic biology and metabolic engineering. [33] Experimental Section Bacterial strains, media, chemicals and culture conditions: E. coli strain Top10F' was used for all experiments. Unless otherwise stated, all chemicals were purchased from Sigma-Aldrich (St Louis, MO, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic biologists envision a future in which combinations of well-characterized sequence elements lead to predictable outcomes, enabling the rational design of biological circuits and novel metabolic pathways (Andrianantoandro et al 2006;Heinemann & Panke 2006;Drubin et al 2007;Sayut et al 2007;Tyo et al 2007). Attempts to characterize and employ sequences that control transcription, mRNA stability and the initiation of translation are underway in many synthetic biology laboratories (Yokobayashi et al 2002;Sprinzak & Elowitz 2005;Heinemann & Panke 2006;Dasika & Maranas 2008;Michalodimitrakis & Isalan 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Overcoming these problems to create functional circuits can require multiple rounds of rational design and extensive changes to the initial circuit, including the replacement of key components. As alternatives to rational design, combinatorial methods provide a way to rapidly generate circuit diversity (17) but are ultimately limited by the small number of well-classified genetic elements (32). Another alternative for the tuning of genetic circuits is the creation and screening of mutant libraries for the key circuit components to identify mutants with properties that mathematical models predict will result in desired behaviors (18,32).…”
mentioning
confidence: 99%
“…This method takes advantage of the ability of models to predict circuit behavior (16,20) but relies on the availability of mutant libraries for the circuit components. Directed evolution is a particularly useful technique for the generation of these mutant libraries as it allows for the rapid generation of diversity that can be used to overcome limited understanding of the complex series of interactions that occur between circuit components (32,41). Here we demonstrate the utility of mutant component libraries in the optimization of circuit function by using a simple mathematical model to identify a set of mutant LuxR proteins from an existing directed evolution library that result in enhancement of the logical responses of the AND gate.…”
mentioning
confidence: 99%
See 1 more Smart Citation